sendo uma funçao definida por f(x) x²-3x-10 calcular :
a) f(-1) b: 1(0) c:f(3)
Usuário anônimo:
na b?
Soluções para a tarefa
Respondido por
3
f(x) = x² - 3x - 10
==============
a) f(- 1)
f(- 1) = (-1)² - 3.( - 1) - 10
f(- 1) = 1 + 3 - 10
f(- 1) = 4 - 10
f (- 1) = - 6
--------------------------------------------------------------------------
b) f(0)
f(0) = 0² - 3.0 - 10
f(0) = 0 - 0 - 10
f(0) = - 10
------------------------------------------------------
c) f(3)
f(3) = 3² - 3.3 - 10
f(3) = 9 - 9 - 10
f(3) = 0 - 10
f(3) = - 10
==============
a) f(- 1)
f(- 1) = (-1)² - 3.( - 1) - 10
f(- 1) = 1 + 3 - 10
f(- 1) = 4 - 10
f (- 1) = - 6
--------------------------------------------------------------------------
b) f(0)
f(0) = 0² - 3.0 - 10
f(0) = 0 - 0 - 10
f(0) = - 10
------------------------------------------------------
c) f(3)
f(3) = 3² - 3.3 - 10
f(3) = 9 - 9 - 10
f(3) = 0 - 10
f(3) = - 10
Perguntas interessantes
Matemática,
9 meses atrás
Biologia,
9 meses atrás
História,
9 meses atrás
Matemática,
1 ano atrás
Psicologia,
1 ano atrás
Matemática,
1 ano atrás